Frequent amplifications of ESR1, ERBB2 and MDM4 in primary invasive lobular breast carcinoma. (1st October 2019) - Cao, Lan; Basudan, Ahmed; Sikora, Matthew J.; Bahreini, Amir; Tasdemir, Nilgun; Levine, Kevin M.; Jankowitz, Rachel C.; McAuliffe, Priscilla F.; Dabbs, David; Haupt, Sue; Haupt, Ygal; Lucas, Peter C.; et al.
Highlights: Comprehensive high-resolution copy number alteration study in primary Invasive Lobular Carcinoma (n = 70). Frequent ESR1 CN gain (14%) or amplification (10%) associated with disease recurrence. Frequent ERBB2 amplification (19%) in primary ILC. Frequent MDM4 amplifications (17%) and a functional role for MDM4 in ILC. These novel findings have potential clinical implications for patients with ILC, an understudied subtype of breast cancer. Abstract: Invasive lobular carcinoma (ILC) is the second most common histological subtype of breast cancer following invasive ductal carcinoma (IDC). To identify potential genetic drivers of ILC progression, we used NanoString nCounter technology to investigate the DNA copy number (CN) in 70 well-curated primary ILC samples. We confirmed prior observations of frequent amplification of CCND1 (33%), and MYC (17%) in ILC, but additionally identified a substantial subset of ILCs with ESR1 and ERBB2 (19%) amplifications. Of interest, tumors with ESR1 CN gains (14%) and amplification (10%) were more likely to recur compared to those with normal CN. Finally, we observed that MDM4 (MDMX) was amplified in 17% of ILC samples. MDM4 knockdown in TP53 wild-type ILC cell lines caused increased apoptosis, decreased proliferation associated with cell cycle arrest, and concomitant activation of TP53 target genes. Similar effects were seen in TP53 mutant cells, indicting a TP53-independent role for MDM4 in ILC. To conclude, amplification of ESR1 and MDM4 are potential genetic drivers of ILC. These amplifications may represent actionable, targetable tumor dependencies, and thus have potential clinical implications and warrant further study.